Dukungan Keluarga pada Lansia di Panti Perlindungan dan Rehabilitasi Sosial Lanjut Usia (PPRSLU) Budi Sejahtera Banjarbaru Tahun 2023 - Anastasia Maratning; Maria Frani Ayu Andari Dias; Mentari Mentari (Jurnal Medika Nusantara, 2024)
The elderly represent a group of individuals undergoing the aging process, and their global population, including Indonesia, continues to increase, as reported by the WHO. Family social support plays a crucial role in maintaining the health and well-being of the elderly. This study aims to provide an overview of family support for the elderly in PPRSLU Budi Sejahtera Banjarbaru. The research adopts a quantitative approach with a target sample size of 89 individuals. However, due to convenience sampling, only 36 respondents could be included in the study. Data collection involved a modified family support questionnaire based on previous research. The result is Out of 36 respondents, 11 individuals (30.5%) reported receiving high family support, while 25 individuals (69.5%) experienced low family support. These findings indicate that the need for family support, particularly in instrumental and emotional aspects, is not entirely met among the elderly in PPRSLU Budi Sejahtera Banjarbaru. The majority of elderly individuals in PPRSLU Budi Sejahtera Banjarbaru experience limitations in family support. Therefore, it is crucial to address these issues and enhance the support provided to the elderly, especially in terms of instrumental and emotional support, to improve their quality of life.